2018
DOI: 10.1016/j.atherosclerosis.2018.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regular endurance exercise on GlycA: Combined analysis of 14 exercise interventions

Abstract: Regular exercise significantly reduced plasma GlycA across 14 different exercise interventions despite differences in exercise programs and study populations. The current study provides a greater understanding of the use of exercise as a potential therapy for the reduction of systemic inflammation. Further research is needed to understand the mechanisms behind the exercise-related reductions in GlycA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…One study mentioned above with a 6-month intervention of resistance exercise alone or combined with diet in overweight and pre-diabetes individuals showed that GlycA levels decreased significantly by 2% [136]. Barber et al demonstrated significantly reduced plasma GlycA in 1568 individuals submitted to 14 exercise interventions even after adjustment for age, sex, race, baseline BMI, and baseline GlycA [137].…”
Section: Effect Of Exercisementioning
confidence: 99%
“…One study mentioned above with a 6-month intervention of resistance exercise alone or combined with diet in overweight and pre-diabetes individuals showed that GlycA levels decreased significantly by 2% [136]. Barber et al demonstrated significantly reduced plasma GlycA in 1568 individuals submitted to 14 exercise interventions even after adjustment for age, sex, race, baseline BMI, and baseline GlycA [137].…”
Section: Effect Of Exercisementioning
confidence: 99%
“…Contrary to findings by Dethlefsen et al [19], we observed lower levels of the chronic inflammatory marker GlycA in CLL-FIT patients and slower in vitro cell growth. GlycA is robustly modifiable by exercise training and is lower in those with higher cardiorespiratory fitness [49,50]. As such, the role inflammation plays on cancer cell growth is complex, and the inflammatory response to exercise which promotes higher physical fitness are equally complex in the cancer setting.…”
Section: Cell Growth In Autologous Plasmamentioning
confidence: 99%
“…Several studies have shown that exercise on a regular basis can change gene expression in various tissues and strengthen the body's protective mechanisms (5). Exercise is able to positively regulate glycoprotein (6).…”
Section: Introductionmentioning
confidence: 99%